2022
DOI: 10.3390/horticulturae8020108
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Analysis of Zinc Finger A20/AN1 Stress-Associated Genes SmSAP Responding to Abiotic Stress in Eggplant

Abstract: Stress-associated proteins (SAP), a class of zinc-finger proteins, have been identified as novel stress regulatory proteins in stress responses. However, SAP genes in eggplant (SmSAP) have been little reported. It has important significance in identifying SAP members, understanding the molecular mechanisms underlying stress responses, and tolerance. We performed a comprehensive study of the A20/AN1 domains, motifs, gene structures, phylogenetic relationships, chromosomal locations, gene replications, collinear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…In present study, 11 SAP genes were identified genome-wide in Jetropha and the phylogenetic divided the JcSAP genes into four groups ( Figure 1 ); Synteny analysis showed that Jatropha SAP genes had a high homology with the Arabidopsis SAP genes ( Figure 2 ). These results are highly in consistence with the previously reported results of [ 1 , 2 ], suggesting very little variation in SAP gene family members.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In present study, 11 SAP genes were identified genome-wide in Jetropha and the phylogenetic divided the JcSAP genes into four groups ( Figure 1 ); Synteny analysis showed that Jatropha SAP genes had a high homology with the Arabidopsis SAP genes ( Figure 2 ). These results are highly in consistence with the previously reported results of [ 1 , 2 ], suggesting very little variation in SAP gene family members.…”
Section: Discussionsupporting
confidence: 92%
“…Stress-associated proteins (SAP) are novel stress regulatory zinc-finger proteins and are strongly associated with tolerance against various abiotic stresses [ 1 , 12 , 13 , 14 , 15 ]. SAP gene family has previously identified and comprehensively studied in many plant species including Oryza sativa [ 5 ], Arabidopsis thaliana [ 5 ], Hordeum vulgare [ 13 ], Glycine max [ 12 ], Gossypium hirsutum [ 16 ], Solanum lycopersicum [ 2 ], Cucumis sativus [ 17 ], Solanum melongena [ 1 ], and Prunus dulcis [ 18 ], etc. However, there is no systematic study of SAP genes in the most important biofuel-producing shrub, Jatropha.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations